Juridical Analysis of Hospital Liability for Doctors’ Negligence in Surgical Operations that Cause Patient Losses Based on Law Number 17 of 2023 concerning Health - Mira Amalina; Andi Adinda Mustafifa; Ayu Sri Rahayu; Ketut Trisandy; Jelly Rita; Fitry Taufiq Sahari (Lembaga Bale Literasi, 2026)
Healthcare is a fundamental right of every citizen and must be provided safely, with quality, and professionally. In practice, surgical procedures carry a high risk of causing harm to patients if negligence is committed by doctors or other medical personnel. Doctors’ negligence in surgical procedures remains one of the legal issues that frequently gives rise to disputes between patients and hospitals. Surgical procedures that are not carried out in accordance with professional standards and standard operating procedures may result in physical and psychological harm, and even the death of the patient. Hospitals are healthcare institutions that play an important role in realizing the highest possible level of public health. As healthcare facilities, hospitals not only provide medical facilities and infrastructure, but also coordinate the various health workers involved in delivering services to patients. In practice, hospitals and health personnel, particularly doctors, have a close relationship in providing healthcare services that are safe, of good quality, and in accordance with professional standards. Therefore, the legal relationship that arises between hospitals, health personnel, and patients is not only related to aspects of medical services, but also to aspects of legal liability when a patient suffers harm. In the development of health law, the concept of hospital liability was initially based on the doctrine of vicarious liability. This doctrine places hospitals as parties responsible for the acts of health workers who work within an employment relationship or under the supervision of the hospital. In other words, mistakes committed by health workers may give rise to liability for the hospital as the employer. However, the increasingly complex development of healthcare systems shows that the doctrine of vicarious liability is not always able to provide optimal legal protection for patients or to answer the various legal problems that arise in the provision of modern healthcare services. Hospitals may be held liable under civil, administrative, and criminal law if negligence causing patient harm is proven. Law Number 17 of 2023 concerning Health strengthens legal protection for patients while expanding the responsibility of healthcare institutions for the quality of the services provided.